Análisis de la producción y comercialización actual de abonos orgánicos y su incidencia para la creación de una planta de producción en la UTEQ, Año 2009 - Cedeño Fuentes, Olga Paola (2010)
The Degree Thesis “Analysis of the Current Production and Marketing of Organic Fertilizers and its Incidence for the Creation of a Plant of Production at UTEQ, 2009 ”, pursued the following objectives: carry out a SWOT analysis of the marketing and production of fertilizers organic, know the current marketing channel, their level of production and how it affects the market, its costs and income, and based on the results propose the application of a production plan and commercialization of organic fertilizers. The research work is development at the State Technical University of Quevedo Campus "La María ”from the City of Quevedo, surveyed students, buyers current organic fertilizers and farmers of the Quevedo canton and its area of influence. The criterion to determine the sample of students from the Faculty of Agrarian Sciences of the UTEQ, was taken based on those students who receive as didactic support in their academic curriculum, the practices of production of organic fertilizers, whose population was 351 students per applying the formula, 23 students were surveyed; I also get to 9 people who bought organic fertilizers in 2009 and finally In order to know the sample of potential clients, the Cantonal Agricultural Center whose total is 150 families, and the organizations Nuevo Lechugal, the Union and Progreso Commune belonging to the UOCQ, which apply organic fertilizers in their cultures were established a total of 97 families for which a target population of 247 people, when applying the formula we surveyed 22 people....................................................................................................................................................................